2017
DOI: 10.3390/catal7110325
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of the Role of Plasma in a Plasma-Coupled Selective Catalytic Reduction of Nitrogen Oxides with a Hydrocarbon Reducing Agent

Abstract: Abstract:The purpose of this study is to explain how plasma improves the performance of selective catalytic reduction (SCR) of nitrogen oxides (NO x ) with a hydrocarbon reducing agent. In the plasma-coupled SCR process, NO x reduction was performed with n-heptane as a reducing agent over Ag/γ-Al 2 O 3 as a catalyst. We found that the plasma decomposes n-heptane into several oxygen-containing products such as acetaldehyde, propionaldehyde and butyraldehyde, which are more reactive than the parent molecule n-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…14 In the plasma discharge zone, the oxidation of HCs is facilitated to form partially oxidized HCs at low temperature, which enhances the reduction of NO x . 15 Furthermore, O radicals, OH radicals, O 3 , and peroxyl radicals (RO 2 , HO 2 ), all of which are reactive chemical species, could be formed in the discharge zone. 16 In exhaust gas, most of the NO x exists in the form of NO, and the SCR of NO x would be promoted by increasing the ratio of NO 2 / NO x in the feed gas.…”
Section: Introductionmentioning
confidence: 99%
“…14 In the plasma discharge zone, the oxidation of HCs is facilitated to form partially oxidized HCs at low temperature, which enhances the reduction of NO x . 15 Furthermore, O radicals, OH radicals, O 3 , and peroxyl radicals (RO 2 , HO 2 ), all of which are reactive chemical species, could be formed in the discharge zone. 16 In exhaust gas, most of the NO x exists in the form of NO, and the SCR of NO x would be promoted by increasing the ratio of NO 2 / NO x in the feed gas.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma coupled with a catalyst, therefore, enables the removal of both NO x and soot at low operating temperatures. Moreover, enhanced NO x removal under fluctuating temperatures was also observed in the presence of plasma [47][48][49][50].…”
Section: Introductionmentioning
confidence: 83%
“…However, the efficiency of NO x removal was not satisfactory with 48 ppm naphthalene tantamount to a C/N ratio of 1.6 (the ratio of carbon concentration in the hydrocarbon to nitrogen concentration in NO x ). Previous reports indicated that n-alkane is an effective reducing agent for the HC-SCR process [48][49][50]. In general, dodecane (C 12 H 26 ) can represent diesel fuel.…”
Section: Removal Of No X and Soot Simulant By Scr Coupled With Plasmamentioning
confidence: 99%
“…This treatment method can not only maintain the catalyst skeleton, remove organic impurities such as template, and prevent the sintering of metal clusters from becoming large, but also has a relatively short processing time compared to conventional roasting. Many experiments have shown that this plasma roasting can replace conventional high-temperature roasting [27,28,29]. …”
Section: Introductionmentioning
confidence: 99%